Estimation of Coal Bed Methane Potential of Coal Seams of Margherita Coal Field, Assam, India - Talukdar, Prasenjit; Das, Ranjan; Goswami, Rishiraj (International Journal of Applied Sciences and Biotechnology, 2015)
The rapid industrialization and growing energy needs have put a great stress on the conventional energy resources. This is even more concerning for a country like India which is a net importer of oil. To meet the ever increasing need for energy, it is essential that the search for unconventional energy is intensified. This paper deals with the estimation of coal bed methane potential of the Margherita Coal Field of Assam, India. For this purpose, eight coal samples were collected from Tirap O.C.P., Ledo UG Incline and Tikak O.C.P collieries of the Margherita coal field. Proximate analysis, megascopic study and finally qualitative analysis of these eight samples was undertaken. After analysis, the inferred reserves of CBM at Margherita Coalfield, was found to be in the range of 42.5-49.04 Billion Cubic Meter. Int J Appl Sci Biotechnol, Vol 3(2): 232-235 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12449